The content quality and educational significance of early childhood caries on short video platforms - Ming-Na Huang; Hong Lu; Ming-Yue Huang; Cai-Yu Li; Yue-Mei Zheng; Dan Wang; Shi-Jun Tang (BMC Public Health)
Abstract Background Early clinical screening and prevention can reduce the incidence and severity of early childhood caries (ECC). With the development of social media, TikTok and Douyin were used as important tools for ECC popularization and early screening. The purpose of this study was to evaluate the educational impact from the integrity, accuracy and quality of ECC-related short videos on TikTok and Douyin. Methods We searched for short videos related to ECC on the mobile application TikTok and Douyin on April 15, 2024. The search keywords were as follows: “Early childhood caries” on TikTok in both English and Japanese, and Chinese search on Douyin. The first 100 short videos were selected as samples for each group. we applied an instrument called DISCERN, which consisted of 3 sections and a total of 16 questions to evaluate the quality of each short video, and used a checklist to rate the content of videos. The accuracy of the content was evaluated based on the Children's Caries Risk Assessment and Management Guidelines. Results A total of 115 short videos were assessed for the useful information quality of ECC, including 78 Chinese, 26 English, and 11 Japanese. The score for the content quality of short videos showed that each of the three groups assigned the highest scores to the sections on symptoms and treatment, with Chinese short videos achieving the top ratings. The DISCERN scores for useful short videos in each group were 33.10 ± 3.49 in Chinese, 29.54 ± 2.37 in English, and 28.27 ± 2.61 in Japanese, respectively. Compared with English and Japanese videos, Chinese videos had the highest DISCERN score with significant differences (p < 0.05). Meanwhile, in Chinese short videos, healthcare professionals or organizations uploaded videos with higher DISCERN scores, which were more comprehensive and extensive than those uploaded by private users. Conclusions It is necessary for more healthcare professionals and institutions to join in to improve the quality of content on short video platforms and solve more health problems for patients through short videos.